PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KHARISMATIK TERHADAP KINERJA KARYAWAN: PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KHARISMATIK TERHADAP KINERJA KARYAWAN - Herlina, Intan Arum; Rahayu, Budi; Kristanti, Desi (Airlangga Journal of Innovation Management, 2024)
As an effort to improve the quality of education, it is closely related to effective leadership and management by a leader. Support from subordinates will be available and sustainable when the leader is truly qualified. A school will be capable of advancing when the leader possesses a vision and mission, managerial abilities, and also integrity in implementing quality enhancements. Moreover, the school further requires quality human resources to fulfill the objectives of an organization. This research aims to test and analyze the influence of democratic and charismatic leadership styles both simultaneously and partially. Methode in this research uses and approach a quantitative approach with multiple linear regression analysis techniques. The population of this study was all 35 employees of MI Jati Salam Jombang, then the sampling technique used was census or total sampling which involved all members of the population as samples. Based on the test results, it was found that democratic and charismatic leadership styles had a positive and significant influence both simultaneously and partially on employee performance. The implications of this research theoretically find that democratic and charismatic leadership styles are theoretically able to influence employee performance but are still influenced by the policies of the organization itself, and practically the application of these two leadership styles must be consistent and continuously improve